Den landoekonomiske Forening for Stamhuset Estrup ved Randers, i Aaret 1850. - Jensen, O. C. (Tidsskrift for Landøkonomi, 2018)
Den landoekonomiske Forening for Stamhuset Estrup ved Randers, i Aaret 1850.